Note on Irreducible Polynomials over $\mathbb{F}_q[X]$ (European Journal of Pure and Applied Mathematics, 2024)
In this note, we provide a new criterion of polynomials's irreducibility over $\mathbb{F}_q[X]$, where $\mathbb{F}_q$ is a finite field.
Keywords: Polynomials,; irreducibility,; criterion,; finite fields